Simulasi Digital Pengoptimalan Waktu Tutup Pintu Saluran Air Menggunakan Motor Stepper Berbasis Mikrokontroler Arduino - Ilham Rizal Ma'arif; Ahmad Nur Fajri; Nur Rani Alham; Bima Sakti (TEKNO: Jurnal Teknologi Elektro dan Kejuruan, 2022)
In the industrial world, it is called as instrumentation to support the performance of an industry. In this research, tools are designed automatically so as to minimize labor requirements and minimize errors if done manually. One of them is a tool designed to control the volume of water in PLTPS so that it does not overflow if excess volume. This control is made in the form of a digital simulation to facilitate understanding and clarify the process flow. In this simulation aims to find the most optimal input voltage used for stepper motors in closing the water channel with the fastest time. To rotate the bisteper at a maximum distance of 448 cm by producing 5 revolutions can be done by providing different input voltages and different times that is when the 2.20s are driven by 2.5 V input voltage, 1.50 s time is driven by 1.88 V voltage, time 2.07 voltage driven 1 V and time 0.35 s voltage driven 0.35 V. The most optimal voltage used is the voltage 1.88 V.